An IL-2-dependent switch between CD95 signaling pathways sensitizes primary human T cells toward CD95-mediated activation-induced cell death - Schmitz, Ingo; Schulze-Bergkamen, Henning; Krammer, Peter H. (The journal of immunology, 2003)
The CD95 (APO-1/Fas) system plays a critical role in activation-induced cell death (AICD) of T cells. We previously described two distinct CD95 (APO-1/Fas) signaling pathways: 1) type I cells show strong death-inducing signaling complex (DISC) formation and mitochondria-independent apoptosis and 2) DISC formation is reduced in type II cells, leading to mitochondria-dependent apoptosis. To investigate the relevance of these pathways, we set up an in vitro model that mimics the initiation and the down phase of an immune response, respectively. Freshly activated human T cells (initiation) are resistant toward CD95-mediated AICD despite high expression of CD95. We previously reported that these T cells show reduced DISC formation. In this study, we show that freshly activated T cells are CD95-type II cells that show high expression levels of Bcl-xL and display a block in the mitochondrial apoptosis pathway. Furthermore, we show that, upon prolonged culture (down phase), human T cells undergo a switch from type II to type I cells that renders T cells sensitive to CD95-mediated AICD. Finally, we demonstrate that this switch is dependent on the presence of IL-2. Our observations reveal for the first time that the existence of coexisting CD95 signaling pathways is of physiological relevance.
Gesehen am 07.04.2021